Sri Lanka : Country Financial Accountability Assessment - World Bank (Washington, DC, 2013)
The framework for public financial accountability in Sri Lanka is founded in the principles of governance associated with the model inherited from the British, widely accepted as appropriate for the country. The primary accountability institutions, and organizations for financial management, control, audit and legislative scrutiny have, however, not evolved in line with the changes in the more advanced democracies of a similar background. This lapse has reduced the effectiveness of the system of public financial accountability in Sri Lanka, resulting in less than adequate assurance, that public funds are used for the purposes intended with due consideration to economy and efficiency. Financial accountability at the sub-national level is less well developed than at the center. The reasons for this are similar to those concerning the central Government, but more acute and pronounced. Public enterprises are characterized by excessive staff; weak management; inefficiencies; heavy losses; dependency on budget transfers; and delayed publication of audited accounts, thus, further eroding public financial accountability. Discussions with stakeholders on reforms, centered around the urgent need to improve public financial accountability, showing five priority areas of concern: 1) Parliamentary control of the public purse has become ineffective, which can be restored by strengthening the oversight function provided by the public accounts and public enterprises committees; 2) the accountability of the executive is too focused on 'spending to budget', rather than on 'managing for results', therefore, introducing, on a progressive basis, a performance based culture with incentives focused on achievement of outputs and outcomes, and, holding government officials accountable for meeting objectives and performance standards should be considered; 3) need for strengthening the public audit function; 4) removing obstacles, and re-visiting the Establishment Code could prod good governance practices; and, 5) addressing greater specificity on financial accounting, reporting, auditing, and capacity building at sub-national levels.